ELECTRONIC EDUCATIONAL RESOURCES AS A MEANS OF FORMATION OF DIGITAL COMPETENCE OF PRIMARY SCHOOL STUDENTS IN THE PROCESS OF ONLINE AND OFFLINE EDUCATION - Blyznyuk, Tetyana; Trotsenko, Olga (Mountain School of Ukrainian Carpaty, 2020)
Today the world is in the process of rapid informatization and digitalization of society in all its spheres. The way and pace of life of a modern man is not similar to the life of previous generations. The spread of the coronavirus disease, known as COVID-19, has necessitated acceptance and adaptation to new working and learning conditions for educators from different countries. Educational institutions around the world are responding to numerous prohibitions and quarantine rules with the transition to distance learning. The crisis has already caused an online boom for education and forced teachers to be prepared to deal with this atypical situation. The most powerful source today is digital technology, or as they call it - digital learning tools, which implies competent use of the latest gadgets. Of course, global changes in public life cannot take place without changes in the educational space, so our education system now follows the experience of advanced European countries and implements many programs for the formation and development of digital literacy, including at the educational level. Definitely, Ukrainian education system follows the experience of advanced New Ukrainian School provides for the widespread use of information and communication technologies by each teacher in their own professional and pedagogical activities, which is an essential way to update and informatize the education content in different education institutions of our country. This process is impossible without the systematic use of electronic educational resources (EER) during the educational process, because they definitely create a modernized content of educational space and provide equal access to educational online materials to each participant in the educational process regardless of location, age or other aspects.